Non-antibiotic antimicrobial polydopamine surface coating to prevent stable biofilm formation on satellite telemetry tags used in cetacean conservation applications - Smies, Ariana; Wales, Jeremy; Hennenfent, Maureen; Lyons, Laura; Dunn, Caleigh; Robbins, Jooke; Lee, Bruce P.; Zerbini, Alexandre; Rajachar, Rupak M. (Frontiers in Marine Science, 2022)
Satellite telemetry tags, used to monitor the migratory behavior of cetaceans, have the potential to be a vehicle for infection due to their invasive nature. Antibiotic coatings have been previously employed to reduce the chances of infection via the formation of a stable biofilm on the surface of the tags. However, increased use of antibiotics has the potential to lead to the development of antibiotic-resistant pathogens. To prevent the formation of antibiotic-resistant pathogens, a polydopamine surface coating that, when exposed to oxygen, releases low doses (~40-100µM) of hydrogen peroxide over a prolonged period (>24 hours) can be used to replace current antibiotic coatings used in the field. These pDA coatings can reduce bacterial adhesion from model bacteria from the two most common genotypes found on the skin of cetaceans (Psychrobacter and Tenacibaculum). The adhesion of Psychrobacter bacteria was reduced by 80% (p<0.01) while Tenacibaculum was reduced by 70% (p<0.001). When the bacteria were dosed with a non-lethal quantity of hydrogen peroxide (200µM) prior to being exposed to pDA surface coatings, there was no decrease in the efficacy of the coatings. This indicates a resistance to hydrogen peroxide will not be formed quickly. Overall, the polydopamine surface coatings were able to reduce the adhesion of model bacteria strains on the surface of medical grade stainless steel, which could increase the functional tag service life while reducing the chances of infection.